A multi-direction pushover procedure for seismic response assessment of low-to-medium-rise modern reinforced concrete buildings with special dual system having torsional irregularity. (December 2020) - Ghayoumian, Golnaz; Emami, Ali R.
Abstract: Current study proposes a new approach for seismic response assessment of torsionally irregular modern buildings with special dual reinforced concrete system by multi-direction pushover analysis. Analytical formulas are developed to define distribution of inter-storey drift, ductility and damage indices in a 3-dimensional perspective wherein the response distributions can be monitored in all the principal/non-principal planar directions at each storey level. The applicability of the approach is examined by developing 3 nonlinear models of 4-, 8- and 12-storey archetypical building structures. The results indicate a substantial reduction of ductility capacity along the non-principal directions close to the plan bisectors of the buildings. Moreover, it is indicated that a constant storey drift limitation may not be always an appropriate acceptance criteria for seismic design purposes. To overcome these challenges, assumption of constant acceptable level of damage is proposed; this is quantified in terms of damage index.